Modifying walking football for people living with dementia: lessons for best practice. Issue 8 (3rd August 2022) - MacRae, R.; Macrae, E.; Carlin, L.
Abstract: Inclusive and modified sport promotes opportunities for participation usually for older people or people with disabilities, physical and or mental health issues. Walking sports, a form of modified sport, is often designed to support engagement in physical and social activity amongst people over 50 years. This qualitative study explored how walking football sessions were designed and delivered for, and experienced by people living with dementia and their family carers. We thematically analysed 18 qualitative interviews and identified three main themes (1) social impact, (2) embodied memories and (3) flexible carer respite. The findings increase our understanding of how walking sports such as football can be viewed as a psychosocial intervention and be modified to promote the inclusion and agency of people living with dementia and respite for family carers. The study offers best practice recommendations for those organising modified sports activities for older people living with dementia.